Genital human papilomavirosis: part I - Passos, Mauro Romero Leal; Almeida, Gutemberg; Giraldo, Paulo César; Cavalcanti, Silvia Maria B.; Cortes Junior, João Carlos; Bravo, Renato S.; Varella, Renata Q.; Fialho, Susana C.A.; Vai, Isabel C.C. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
In recent decades, some diseases have reached epidemic proportions worldwide. Among these pandemics, genital infection by Human Papillomavirus (HPV) can be highlighted. HPV infection is usually asymptomatic and, in most cases, is transient, since the immune system may be able to fight the infectious process by either solving it or inactivating it. Several types of HPV cause genital lesions, and can be manifested as, for example, a condyloma acuminata. Some genital lesions can be associated to persistent infection and development of intraepithelial neoplasia and even cancer in time. For many years, there has been a demand for a definite therapy to treat HPV. Nowadays, the options range from the ablation of the lesion to its destruction with chemical or physical agents. Based on the frequency with which genital HPV infection manifests itself in the population, its many clinical aspects and the advances of new options to approach these diseases, it has become a continuous research focus. Several types of treatment are available for genital HPV lesions, ranging from the cytodestructive treatments to those carried out by surgical excision. The use of self and domestic applicable products can present good results for the patient. The availability of HPV vaccines for the population may be the beginning of a new era in the primary prevention of HPV infection. However, the millions of cases of HPV infection, especially the condyloma acuminatum will be responsible for many years of hard work treating those already infected. This article, Part I, attempts to carry out a comprehensive review on the main pathogenic, clinical, diagnostic, treatment and prophylactic aspects of HPV genital lesions.